ANALISIS EFISIENSI BANK PEMBIAYAAN RAKYAT SYARIAH DI PROVINSI JAWA BARAT PERIODE 2016-2019 - Dina Uswatun Hasanah; Ibdalsyah Ibdalsyah; Ikhwan Hamdani (Kasaba, 2020)
Development of BPRS can be developed quantitatively through BPRS financial ratios. The BPRS has a high BOPO which proves that the BPRS experiences financing and inefficient performance problems. This study aims to measure the efficiency of BPRS in West Java for the period 2016-2019. This type of research is quantitative research with non-parametric Data Envelopment Analysis (DEA). Source of data used is secondary data collected from financial statements issued by the OJK. The sampling technique used in this study was purposive sampling by taking 11 BPRS samples. The results of this study indicate that of 44 UPBs, 8 UPBs (18.19%) are at the efficiency point as a whole, 14 UPBs (31.81%) are technically efficient, and 9 DMUs (20.45%) are efficient. in scale. The factor causing the inefficiency of the BPRS in West Java is the inadequate use of inputs.